Pressure effects in the Raman spectra of La2-xSrxCuO4 - Lampakis, D.; Liarokapis, E.; Lykodimos, V.; Panagopoulos, C (High Pressure Research, 2002)
Micro-Raman measurements under hydrostatic pressures up to 6GPa have been carried out on high-quality La2-xSrxCuO4 polycrystalline compounds with Sr concentration up to x=0.45. The zz scattering polarization has been investigated, where two strong modes due to La/Sr and the apex oxygen, and (in the low Sr concentrations) the soft mode at ≃100cm-1 are observed. The frequency of the strong modes increases almost linearly with pressure for the Sr concentrations studied. Modifications in the increment rate dω/dp and the phonon width have been detected depending on the amount of doping. For x=0.45 a considerable increase in the width of both strong phonons with pressure was found, which must reflect a separation into phases, since this concentration is close to the solubility limit. The relative intensity of the strong phonons was investigated in connection with its correlation to the transition temperature.
cited By 1